(untitled) (Revista Electrónica REDINE, 2018)
The present research shows the direct relationship that must exist between the teaching plant and the management of the existing curriculum in UNELLEZ-Barinas, a study that is fundamental in view of the current need to train teachers able to use the new technologies reported And communication as a horizon of possibilities that allows to incorporate a new means for the strengthening of the process of teaching-learning. The study will be performed under the quantitative paradigm; Is based on field research, with non-experimental design. For the interpretation of the results, descriptive statistics will be used. The study shows that teachers are more willing to comply and succeed in activities that go hand in hand with changing the old conception of the curriculum and teaching methods by the Teacher by implementing the necessary technologies.